Advances in Transition-Metal-Catalyzed C–H Bond Oxygenation of Amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis, 2021)
C–O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C–H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C–H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp2)–H and C(sp3)–H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp2)–H oxygenation and (ii) C(sp3)–H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.1 Introduction2 C(sp2)–H Oxygenation2.1 Monodentate Directed2.2 Bidentate Directed3 C(sp3)–H Oxygenation3.1 Monodentate Directed3.2 Bidentate Directed4 Conclusion and Outlook
Keywords: amides; C–H activation; directing group; oxygenation; transition metal